Study of the stability of 1alkyl-3-methylimidazolium hexafluoroantimonate(V) based ionic liquids using xray photoelectron spectroscopy - Longo Jr, Luiz S.; Smith, Emily F.; Licence, Peter (American Chemical Society, 2016)
A series of highly pure 1-alkyl-3-methylimidazolium hexafluoroantimonate (V) ionic liquids was firstly investigated by XPS. Reliable binding energy values for all elements within the samples were obtained by applying a C 1s fitting model previously employed for other imidazolium ionic liquids, based on setting the C 1s aliphatic component to 285.0 eV when alkyl chains are longer than 8 carbons. We also observed a straightforward X-ray-mediated photoreduction of Sb (V) to Sb (III) species, i.e. reduction of [SbF6]- anion to volatile SbF3. Thus, binding energies values observed at 542.5 eV and 533.1 eV were attributed to Sb 3d3/2 (V) and Sb 3d5/2 (V), respectively, whereas values at 541.0 eV and 531.7 eV were found for Sb 3d3/2 (III) and Sb 3d5/2 (III), respectively. The SbF3 being formed can be lost either by evaporation and/or redistribution to the bulk. Providing the sample is cooled to freezing temperatures, the SbF3 is prevented from escaping the ionic liquid and it accumulated on the surface of cooled [C4C1Im][SbF6] and [C8C1Im][SbF6]. Particularly in the case of prolonged X-ray exposure of a cooled [C4C1Im][SbF6], an unprecedented further reduction of Sb (III) to Sb (0) was noticed. This study provides fundamental knowledge on the XPS data for antimony compounds as well as providing a step towards the surface analysis of materials composed by antimony species, notably the hexafluoroantimonate (V) anion.